Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening di Bagian Gudang pada PT. Sarijasa Transutama Jakarta - Lukiyana Lukiyana; Firman Davi Firdaus (Majalah Ilmiah Bijak, 2017)
This research was conducted to measure the Influence Workload and Working Environment on Employee Job Performance with Job Satisfaction as an intervening variable in PT . Sarijasa Transutama Jakarta warehouse. The sample studied totaled 68 respondents. This study uses qualitative analysis and quantitative analysis. Testing is done with the system simultaneously and partially. The analysis showed that the work load significantly influence employee performance, the working environment have a significant effect on employee performance, workload and working environment together - each has a significant influence on employee performance, intervention job satisfaction may mediate the effect of workload on achievement work, job satisfaction interventions may mediate the effect of the work environment on work performance.